2012
DOI: 10.1210/jc.2011-2512
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Overall Survival of Radioactive Iodine in Low-Risk Differentiated Thyroid Cancer Patients

Abstract: With a long-term follow-up of 10.3 yr, we failed to prove any survival benefit of RAI after surgery in a large cohort of low-risk DTC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(107 citation statements)
references
References 27 publications
4
100
0
3
Order By: Relevance
“…The mean dose of RAI used was 90mCi. 26 Another retrospective study assessing low-risk PTC patients, of whom only 55% had macrocarcinoma and who were not treated with RAI, found a structural recurrence rate of 2.3%. 27 The current ATA guidelines report that "RAI remnant ablation is not routinely recommended after thyroidectomy for ATA low-risk DTC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean dose of RAI used was 90mCi. 26 Another retrospective study assessing low-risk PTC patients, of whom only 55% had macrocarcinoma and who were not treated with RAI, found a structural recurrence rate of 2.3%. 27 The current ATA guidelines report that "RAI remnant ablation is not routinely recommended after thyroidectomy for ATA low-risk DTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,16,25 The overall mortality in low-risk DTC patients for a median follow-up of 10 years is approximately 5%, either with or without RAI ablation. 26 Furthermore, several studies and meta-analyses have demonstrated that postoperative RAI administration in low-risk DTC patients fails to improve the overall survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Un estudio retrospectivo multicéntrico, donde se evaluaron 1,298 pacientes de bajo riesgo, con un seguimiento promedio de 10.3 años, no encontró beneficios de la ablación con yodo 131 en relación con la supervivencia global y la supervivencia libre de progresión 35 . En concreto, existe poca evidencia que apoye el uso de yodo 131 en estos pacientes.…”
Section: Pacientes De Riesgo Bajounclassified
“…However, National Thyroid Cancer Treatment Cooperative Study Group (NTCTCSG) published data of 4,767 patients with >5 year follow-up in 2010 with a revised conclusion of no significant impact of RAI ablation upon survival of low risk patients (Jonklaas et al, 2010). NTCTCSG also ruled out its previous findings published in 2006 showing adverse effect of RAI on over-all survival in low risk patient (Schvartz et al, 2012 failed to prove any survival benefit of RAI after surgery in low risk group with WDTC. So the controversy is still on about the use of RAI in low risk patients with WDTC as available data are fueled by retrospective and non-randomized clinical studies.…”
Section: Remnant Ablation or Not In Low Risk Wdtc?mentioning
confidence: 99%